2019
DOI: 10.26682/sjuod.2019.22.2.25
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge And Attitude of Nurses about Neonatal Hyperbilirubinemia in Duhok Governorate: Cross Sectional Study

Abstract: Background and objectives: Neonatal hyperbilirubinemia is the most common medical condition in the neonates. About 60% of term and 80% of preterm infants develop jaundice during 1st week of life. The objectives of the study were to assess knowledge and attitude of nurses toward hyperbilirubinemia , and to find out whether there were any relationships between nurses knowledge and attitude with sociodemographic data. Subjects and methods: A descriptive, cross sectional study was done all nurses (n=166) working i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…A cross-sectional study conducted in Kurdistan, Iraq, among 166 nurses reported satisfactory knowledge on NNJ including phototherapy treatment (59.0%), causes (47.0%), and guidelines for management (75.3%). The study equally reported good knowledge of nurses on the clinical presentation of NNJ (98.8%), physical examination (82.5%), accompanying complications (47.0%), and nursing care practices (95.8%) ( Mirza & Atrushi, 2019 ). Another cross-sectional study involving 60 staff nurses in Mysuru, India, showed an average knowledge (51.66%) of NNJ and significant association between participants’ knowledge and years of experience and unit where they work ( Chandrasekhar et al, 2017 ).…”
Section: Literature Reviewmentioning
confidence: 85%
See 2 more Smart Citations
“…A cross-sectional study conducted in Kurdistan, Iraq, among 166 nurses reported satisfactory knowledge on NNJ including phototherapy treatment (59.0%), causes (47.0%), and guidelines for management (75.3%). The study equally reported good knowledge of nurses on the clinical presentation of NNJ (98.8%), physical examination (82.5%), accompanying complications (47.0%), and nursing care practices (95.8%) ( Mirza & Atrushi, 2019 ). Another cross-sectional study involving 60 staff nurses in Mysuru, India, showed an average knowledge (51.66%) of NNJ and significant association between participants’ knowledge and years of experience and unit where they work ( Chandrasekhar et al, 2017 ).…”
Section: Literature Reviewmentioning
confidence: 85%
“…Effective delivery of light, correct positioning of the baby, adequate skin exposure, maintaining proper hydration, daily weighing, and promoting interaction between parents and the neonate are also important nursing care practices for managing NNJ ( Ghada et al, 2016 ; Stark & Lannon, 2009 ; Yost, 2017 ). Mirza and Atrushi (2019) conducted a study in Kurdistan, Iraq, among 166 nurses and found that only 12.7% had a positive attitude towards NNJ, while the majority (87.3%) held a neutral attitude. According to Ahmed and Hani (2017) , among 41 nurses in Minia, Egypt, the common nursing care practices towards NNJ included phototherapy, proper covering and shielding of gonad, appropriate positioning of neonates, and assessment and regulation of thermoregulation device.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation